Factors and Mechanisms Involved in Acquired Developmental Defects of Enamel: A Scoping Review - Collignon, Anne-Margaux; Vergnes, Jean-Noël; Germa, Alice; Azogui, Sylvie; Breinig, Sophie; Hollande, Clémence; Bonnet, Anne-Laure; Nabet, Cathy (Frontiers in Pediatrics, 2022)
Background: Developmental Defects of Enamel (DDE) is a pathology of the teeth that can greatly alter the quality of life of patients (hypersensitivity, esthetic issues, loss of function, etc.). The acquired DDE may occur as a result of a wide range of acquired etiological factors and his prevalence of this pathology may reach up to 89.9%. The main objective of this research was to identify and analyze, in current literature, the factors related to acquired DDE, in order to propose a general theory about the mechanisms involved. Methods: The search of the primary literature was conducted until [December 31,2021]. Our search strategy uses the Pubmed/MEDLINE database and was structured around 3 terms [“Development”, “Defect”, and “Enamel”]. To be included, references had to be primary studies, written in English. Exclusion criteria were reviews, in vitro, animal, genetic or archeology studies, and studies focused on clinical management of DDE. 123 articles were included in this scoping review: 4 Randomized clinical trials, 1 letter, 5 cases reports, 2 fundamentals studies and 111 observational studies (33 Cross-sectional studies, 68 Cohort study and 10 Case-control study). The quality of evidence was assessed using the PEDro scale for clinical trials, the Newcastle-Ottawa scale for observational studies, and a published tool to assess the quality of case reports and case series. Results: A scoping review of the literature identified 114 factors potentially involved in acquired DDE. The most frequently encountered pathologies are those causing a disorder of calcium homeostasis or a perturbation of the ARNT pathway in mother or child. The link between the ARNT pathway and metabolism deficiency in uncertain and needs to be defined. Also, the implication of this mechanism in tissue impairment is still unclear and needs to be explored. Conclusions: By identifying and grouping the risk factors cited in the literature, this taxonomy and the hypotheses related to the mechanism allow health practitioners to adopt behaviors that limit the risk of developing aDDE and to set up a prevention of dental pathology. In addition, by reviewing the current literature, this work provides guidance for basic research, clinical studies, and literature searches